Beitrag zur Kenntnis einiger Bohrfliegenlarven (Diptera: Trypetidae). - Dirlbek, Karel; Dirlbek, Jan (Contributions to Entomology = Beiträge zur Entomologie, 1962)
There are given descriptions of 6 species of Trypetidae with figures of the prae- and poststigmata and the cephalopharyngeal skeleton. The characters of larvae in connection with their biology were found to correspond with the literature studied. The position of prae- and poststigmata and cephalopharyngeal skeleton of the root parasite Orellia jalcata Scop. shows some resemblance to these characters in species living on fruits.